PEMEKATAN ENZIM SELULASE Penicillium sp. LBKURCC20 DENGAN PENGENDAPAN AMONIUM SULFAT 80% JENUH - Masdalena Sinaga; Titania T. Nugroho; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cellulase enzyme activity of Penicillium sp. LBKURCC20 Isolate of Riau can beincreased by concentrating the enzyme using 80% saturated solid ammonium sulfate(NH 4 ) 2 SO 4 anhydrous. Precipitated enzyme was redissolved by the addition of acetatebuffer solution pH 5.5 to 1/70 times its original volume. Cellulase enzyme activity wasdetermined using substrates CMC and avicel. CMCase and avicelase enzyme activity ofthe crude enzyme was (0.0164 ± 0.0036) U/mL and (0.003 ± 0.0025) U/mL,respectively. CMCase and avicelase enzyme activity after concentration was (0.219 ±0.0579) U/mL and (0.03 ± 0.03) U/mL, respectively. The test results showed that theactivity of concentrated CMCase increased 13.5 times and avicelase enzyme activityincreased 10 times after concentrating.